1968
DOI: 10.1007/bf02541246
|View full text |Cite
|
Sign up to set email alerts
|

The effect of various concentrations of tocopherols and tocopherol mixtures on the oxidative stability of a sample of lard

Abstract: A comparison was made of α‐, γ‐, and δ‐tocopherol at various concentrations and a mixture of these tocopherols representing the average tocopherol content of peanut oil on the oxidative stability of lard at 97C. Uptake of oxygen was used to indicate the length of the induction period. The antioxidant effectiveness of the tocopherols was found to increase in the order α, δ, γ. The antioxidant efficiency decreases with increasing concentrations of tocopherols such that addition of any single tocopherol above a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 8 publications
6
26
1
Order By: Relevance
“…But oxidation increased sharply when oils contained 284 to 473 ppm δ-tocopherol at 60°C (P < 0.05). We speculated that the optimal concentration for δ-tocopherol may exist below 500 ppm, but this disagrees with earlier reports (5,(7)(8)(9)(10). The earlier studies showed that the antioxidant activity of δ-tocopherol increased with concentration (from 100 to 500 ppm) and exhibited no optimal concentration over this concentration range.…”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation
“…But oxidation increased sharply when oils contained 284 to 473 ppm δ-tocopherol at 60°C (P < 0.05). We speculated that the optimal concentration for δ-tocopherol may exist below 500 ppm, but this disagrees with earlier reports (5,(7)(8)(9)(10). The earlier studies showed that the antioxidant activity of δ-tocopherol increased with concentration (from 100 to 500 ppm) and exhibited no optimal concentration over this concentration range.…”
Section: Resultscontrasting
confidence: 77%
“…For example, α-tocopherol exhibits optimal antioxidant activity at concentrations between 100 and 250 ppm (4)(5)(6). The optimal concentration for γ-tocopherol is between 250 and 500 ppm (4)(5)(6)(7), and the optimal concentration for δ-tocopherol is between 500 and 1000 ppm (5,(7)(8)(9)(10). The optimal concentration for the mixture of tocopherol homologues present in soybean oil is between 500 and 750 ppm (9,11).…”
mentioning
confidence: 99%
“…Similar findings had also been reported by Cort 17 ) working with chicken fat added dex-and d/-ex-tocopherol and by Parkhurst et a/. 18 ) working with lard added ex-, y-, and btocopherol.…”
Section: Resultssupporting
confidence: 86%
“…The chemical structures of the tocopherols and tocotrienols gives a hydrogen donating power in the order a > P > y > 8 (32). This order of acivity was also observed in a homogenous solution in dichlorobenzene (31) but the order was reverse in fats, oils and lipoproteins in vitro (33)(34)(35)(36)(37)(38)(39) The presence of the phenolic hydroxyl in tocopherols and tocotrienols is critical for activity, but there is no agreement on its role. When the hydroxyl group is masked a total loss of activity is seen.…”
Section: Biopotencymentioning
confidence: 93%